Panduan Teknik Relaksasi Benson pada Pasien Hemodialisis: Literature Review - Ratna Wirawati Rosyida; Sa’bani N. Ardliyah; Umi Pebriyana Parwanti; Sitti Ramdasari Aksan; Ruly Anita Sari; Jony Fransisco Dos Santos Silva; Surya Nova Rosadi; Siti Na’imah; Sri Wahyuni; Tati Hardiyani; Santalia Banne Tondok; Zulfa Mahdiyatur Rasyida; Yayu Nidaul Fithriyyah (PSIK FKKMK UGM, 2020)
Background: Hemodialysis is the most common method applied to patients with chronic kidney failure. But the method has a huge impact on the patient’s health. The Benson relaxation technique is a cheap and simple therapy to reduce the effects of hemodialysis procedures. Objective: This research aims to provide guidance on the application of Benson relaxation techniques for chronic kidney disease patients undergoing hemodialysis. Method: The preparation of the guide starts with defining key questions. A literature search was conducted through five databases: ScienceDirect, PubMed, Scopus, Clinical Key, and the Cochrane Library. Duplicate articles are screened. The snowball method is used by looking at the references in each literature. Inclusion criteria: articles according to key questions, in English, within the last 5 years, and original research. Exclusion criteria: without the principle of muscle relaxation, not speaking English, and not being a study on hemodialysis patients. The study quality used The Joanna Briggs Institute (JBI) Critical Appraisal Tools. Data extraction by one author, cross-verification by another. Data were classified to level of evidence I-V according to the Joanna Briggs Institute (JBI). Recommendations are prepared according to the level of evidence. Result: Found 15 articles that are relevant to the research question. Among them 12 articles are Randomized Controlled Trial (RCT) while 3 other articles are quasi-experimental. Based on the level of The Joanna Briggs Institute evidence, 12 articles are categorized as level 1C and 3 articles are level 2C. The results of the literature show that guidelines can be designed including patient selection criteria, optimal duration, implementation time, preparation steps, procedures, benefits, and side effects of the technique. Conclusion: The Benson relaxation technique has benefits for chronic kidney failure patients undergoing hemodialysis and this guide can be used as a reference by health practitioners.ABSTRAKLatar belakang: Hemodialisis merupakan metode paling umum diterapkan pada pasien gagal ginjal kronis. Namun metode tersebut berdampak besar pada kesehatan pasien. Teknik relaksasi Benson merupakan terapi yang murah dan sederhana untuk mengurangi dampak prosedur hemodialisis. Tujuan: Penelitian ini bertujuan memberikan panduan penerapan teknik relaksasi Benson pada pasien gagal ginjal kronis yang menjalani hemodialisis. Metode: Penyusunan panduan dimulai dengan menetapkan pertanyaan kunci. Pencarian literatur dilakukan melalui lima database: ScienceDirect, PubMed, Scopus, Clinical Key, dan Cochrane Library. Artikel duplikat diskrining. Metode Snowball digunakan dengan melihat referensi dalam setiap literatur. Kriteria inklusi: artikel sesuai pertanyaan kunci, berbahasa Inggris, dalam 5 tahun terakhir, dan paper penelitian. Kriteria eksklusi: tanpa prinsip relaksasi otot, bukan berbahasa Inggris, dan bukan penelitian pada pasien hemodialisis. Penilaian kualitas studi menggunakan The Joanna Briggs Institute (JBI) Critical Appraisal Tools. Ekstraksi data oleh satu penulis, verifikasi silang oleh yang lain. Data diklasifikasikan ke tingkat evidence I-V sesuai The Joanna Briggs Institute (JBI). Rekomendasi disusun sesuai tingkat evidence. Hasil: Ditemukan 15 artikel yang relevan dengan pertanyaan penelitian. Dua belas artikel merupakan Randomized Controlled Trial (RCT) sementara 3 artikel lainnya kuasi-eksperimental. Berdasarkan tingkatan evidence The Joanna Briggs Institute, 12 artikel diklasifikasikan level bukti 1C dan 3 artikel level 2C. Hasil literatur menunjukkan panduan dapat dirancang mencakup kriteria seleksi pasien, durasi yang optimal, waktu pelaksanaan, langkah persiapan, prosedur, manfaat, dan efek samping teknik tersebut. Kesimpulan: Teknik relaksasi Benson memiliki manfaat bagi pasien gagal ginjal kronis yang menjalani hemodialisis dan panduan ini dapat dijadikan referensi oleh praktisi kesehatan.